Enhancing Student’s Motivation Through Spada Moodle E-Learning - Azizah Husda; Yola Asmoro; Meilan Simanullang; Nur Lestari Br. Situngkir (Peneliti.net, 2022)
This research is intended for English language education students who are doing bold learning during the covid-19 pandemic. Learning that should be done face-to-face must now be oriented to distance learning. Circumstances that require students to use internet network technology, namely the use of SPADA MOODLE E-learning, SPADA MOODLE E-learning is a site that has been provided for students to take bold learning. In this study, the researcher used a descriptive qualitative method by distributing a questionnaire in the form of a google form to make it more accessible to students. This study aims to determine student motivation in participating in bold learning during the covid-19 pandemic. This research is expected to provide evaluations from various organizers who are brave in higher education, especially those involving increasing the learning motivation of English education students.